Meningkatkan Hasil Belajar Praktek Tari Galombang Melalui Media Audio Visual di Kelas VII (A) SMP Negeri 22 Padang - Gia Widi Ayuni; Syeilendra Syeilendra (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The purpose of this study is to find out students' dance skills after using a video platform in learning Galombang dance in class VII (A) SMP Negeri 22 Padang. This type of research is classroom action research. This research uses 2 cycles which include planning, implementation, observation and reflection. Data collection methods include observations, interviews and documents. The data was analyzed using a percentage formula. The results of the study prove that the use of visual media in dance education can increase learning outcomes and facilitate learning. It is said that students' abilities have increased from cycle I to cycle II, namely in cycle I the average score is 81.72, the percentage (44%) of students have achieved compliance, but (56%) of students. In the second cycle, students increased and reached KKM > 78, with an average score of 96.33 and the percentage (100%). Therefore, all students should achieve KKM > 78. It is known that practice in the classroom using props adds to the learning results of Galombang dance cultural arts students. In this way, video and audio platforms should be used to transform the teaching and learning environment to be more efficient, effective and engaging